Luxury Brand Charisma - Hatton-Jones, Siobhan (Curtin University, 2020)
This research developed a scale to measure luxury brand charisma, by advancing the known research about the specific phenomenon of charisma into a luxury marketing and branding context. The development of the scale demonstrated the advanced use of qualitative and quantitative skills required to successfully conduct the research design, from concept. This research provides significant advancement to the theory and body of knowledge; in addition to the management and strategy decisions of luxury brand managers.